Microbial Eukaryotes in the Human Microbiome: Ecology, Evolution, and Future Directions - Wegener Parfrey, Laura; Walters, William A.; Knight, Rob (Frontiers in Microbiology, 2011)
High throughput sequencing technology has opened a window into the vast communities of bacteria that live on and in humans, demonstrating tremendous variability and that they play a large role in health and disease. The eukaryotic component of the human gut microbiome remains relatively unexplored with these methods, but turning these tools toward microbial eukaryotes in the gut will likely yield myriad insights into disease states as well as the ecological and evolutionary principles that govern the gut microbiota. Microbial eukaryotes are common inhabitants of the human gut worldwide and parasitic taxa are a major source of morbidity and mortality, especially in developing countries, though there are also many taxa that cause no harm or are beneficial. While the role microbial eukaryotes play in healthy individuals is much less clear, there are likely many complex interactions between the bacterial, archaeal, and eukaryotic components of the human microbiome that influence health and disease states. Integrating eukaryotic microbes into a broad view of microbiome function requires an integrated ecological approach rather than one focused on specific, disease-causing taxa. Moving forward, we expect broad surveys of the eukaryotic microbiota and associated bacteria from geographically and socioeconomically diverse populations to paint a more complete picture of the human gut microbiome in health and disease.